Inside Cover: Quantification of Redox Sites during Catalytic Propane Oxychlorination by Operando EPR Spectroscopy (Angew. Chem. Int. Ed. 7/2021). Issue 7 (4th January 2021) - Zichittella, Guido; Polyhach, Yevhen; Tschaggelar, René; Jeschke, Gunnar; Pérez‐Ramírez, Javier
Abstract : Operando EPR gets hot In their Research Article on page 3596, Guido Zichittella, Yevhen Polyhach, Javier Pérez‐Ramírez, and co‐workers demonstrate operando EPR spectroscopy as a pivotal technique to assess the oxidation state of CrPO4 and EuOCl catalysts during high‐temperature catalytic propane oxychlorination. As depicted in the cover picture, this enables the quantification of catalytically active centers, as the redox couple Cr 3+  (gold)/Cr 2+  (lilac), whose formation was correlated with the productivity of propylene.